Circumvitellatrema momota n. gen., n. sp. (Digenea: Cyclocoelidae: Cyclocoelinae) from a captive-hatched blue-crowned motmot, Momotus momota (Momotidae) - Dronen, Norman O.; Greiner, Ellis C.; Ialeggio, Donna M.; Nolan, Thomas J. (Zootaxa, 2009)
Circumvitellatrema momota n. gen., n. sp. was found in the air sacs of a captive-hatched blue-crowned motmot, Momotus momota (Momotidae), that was being maintained in quarantine at the Animal Health Center of the Philadelphia Zoo in Philadelphia, Pennsylvania, U.S.A. This bird apparently became infected at the Audubon Zoo, New Orleans, Louisiana, U.S.A. where it was maintained for several years prior to being sent to the Philadelphia Zoo. In the new genus, the ovary is intertesticular, forming a triangle with the testes and the genus is assigned to Cyclocoelinae. It can be distinguished from the other 3 genera currently assigned to this subfamily (Cyclocoelum, Psophiatrema, and Selfcoelum) by having the vitelline fields confluent at both the anterior and posterior ends of the body forming a continuous loop. This new species was likely introduced into the Audubon Zoo through the importation of species of exotic birds.